Academic Senate Minutes 2002-03-21 - Academic Senate:::::::::
Agenda and minutes approved. Presentation on Diversity at SSU by Larry Shinagawa. SBC resolution on the Development tabled indefinitely. SBC resolution on marginal cost formula withdrawn, SBC resolution on the Preservation of Access, Affordability, and Quality approved. FSAC's Evaluation of Temporary Faculty document referred back to FSAC with substitute document. Resolution for Jim Meyer, Vice President of Development approved. Speeches and reception for Jim Meyer.